Pemilihan Siswa Berprestasi Menggunakan Analisis Metode SAW, WASPAS, dan WP - Prayogo, M. Ari; Subastian, Eko; Annafi, Naufal (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The problem in this research is that the selection process for achievement students often faces obstacles, including data processing and the risk of human error. With this research, it can be used as very good input for selecting achievement students because it uses the Simple Additive Weighting calculation method analysis or commonly called SAW, Weighted Aggregated Sum Product ASsesment or commonly called WASPAS, and Weighted Product or commonly called WP. The purpose of this study is to apply calculation analysis using the SAW, WASPAS, and WP methods to select achievement students in schools. These three methods are applied to determine the ranking of achievement students based on a number of predetermined criteria. There are 7 alternative students who will be determined as one of the achievement students. There are also criteria used to select achievement students, namely based on average report card scores, class rankings, attitude and discipline scores, participation in organizations, and competition winners. Of the 5 criteria used as the basis for selecting one of the achievement students at the school. The results obtained based on the analysis of calculations using the SAW, WASPAS, and WP methods, that a student named Muhammad Rizky Amanullah (A3) was named an achievement student among other students. Students obtained the highest score in the SAW Method with a Vi value of 0.950, then the WASPAS Method with a Qi value of 0.947, and the WP Method with a Vi value of 0.186. From the results obtained, this study can provide input and recommendations in terms of selecting achievement students in schools.